Band-Gap and Dimensional Engineering in Lead-Free Inorganic Halide Double Perovskite Cs4Cu1-xAg2xSb2Cl12 Single Crystals and Nanocrystals - Zhou, Wei; Han, Peigeng; Luo, Cheng; Li, Cheng; Hou, Jie; Yu, Yang; Lu, Ruifeng (Frontiers in Materials, 2022)
Lead free double perovskites (DPs) are promising materials due to their non-toxic and tunable optical properties. In this work, a series of lead-free halide DP single crystals (SCs) and nanocrystals (NCs) (Cs4Cu1-xAg2xSb2Cl12) were reported. With alloying strategy, the optical band-gap engineering was realized and the dimension can be controlled between 2D and 3D. The Cu-alloyed SCs exhibit strong absorption from the UV-visible region to the near-infrared range (can even completely cover the bands of NIR-I and NIR-II). In addition, (Cs4Cu1-xAg2xSb2Cl12) NCs were synthesized via a top-down approach, which maintains similar optical properties and the dimensional transformation phenomenon to SCs. These results suggest the great potential of Cs4Cu1-xAg2xSb2Cl12 SCs and NCs for photovoltaic and optoelectronic applications.